Bromelain Supplementation in the Management of Otitis Media with Effusion in Children - Francesco Martines; Ginevra Malta; Emanuele Cannizzaro; Theodoridou Kelly; Pietro Salvago; Fulvio Plescia (Children, 2024)
Background/Objectives: The respiratory system is prone to infectious diseases, especially in children below five years of age. Upper respiratory tract infections in children are often associated with Eustachian tube dysfunction and complicated by otitis media with effusion (OME), an inflammatory process within the middle ear, which can lead to hearing loss. Treatment for these infections involves a combination of medication and symptom relief, depending on the severity and cause of the infection. In recent years, natural therapeutic drugs derived from herbal medicines have been gaining popularity in treating various pathologies. Bromelain, one of the most studied natural compounds, has been investigated extensively due to its numerous pharmacological properties, offering a potential new avenue for treatment. Based on these promising findings, our study was designed to examine the efficacy of supplementation with bromelain in countering symptoms associated with OME. Methods: This study was conducted on data acquired from medical records from the Section of Audiology of the University of Palermo, focusing on the period of January 2022 to June 2023 and selecting 224 children (age range 1–8 years), namely 174 males and 50 females, who were evaluated for presumed OME at the audiology pediatric ambulatory. All patients selected before initiating pharmacological treatment underwent thorough screening regarding the functionality of the tympanic cavities, otoacoustic emissions, the auditory threshold, and the ear canal’s integrity. Results: The preliminary findings of this study are significant, demonstrating that supplementation with bromelain led to notable improvements in the symptoms accompanying OME after 15 days and 60 days of therapy. Notably, patients who received the bromelain supplement reported reduced mucus secretions and improved auditory function. Conclusions: These results underscore the potential of naturally occurring compounds as adjuvants to standard therapeutic strategies in treating OME.